2018
DOI: 10.1007/s12161-018-1208-z
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic MS/MS Analysis of a Large Group of Insecticides in Honey by Modified QuEChERS

Abstract: The analytical tool for analysis of pesticide residues in honey must still be improved. Therefore, a sensitive, selective, rapid, and reliable analytical method for the analysis of pesticide residue belonging to 29 different classes at very low concentration levels was developed. Over 130 insecticides were extracted from the honey matrix using different amounts of sample, concentrations of the extraction solvent, and cleanup sorbents. Acceptable extraction recoveries accounting for matrix effect were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The QuEChERS method was applied for pesticide extraction in honey by other authors [ 26 , 27 , 28 , 29 , 30 , 41 , 42 ]. The LC-MS/MS method described by Souza Tette et al [ 28 ] was validated to measure 116 pesticides in honey, but 11 compounds showed recoveries at 0.010 mg/kg out of the 70–120% range.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The QuEChERS method was applied for pesticide extraction in honey by other authors [ 26 , 27 , 28 , 29 , 30 , 41 , 42 ]. The LC-MS/MS method described by Souza Tette et al [ 28 ] was validated to measure 116 pesticides in honey, but 11 compounds showed recoveries at 0.010 mg/kg out of the 70–120% range.…”
Section: Resultsmentioning
confidence: 99%
“…However, the LOD was not reported, and some pesticides showed recoveries out of the 70–120% range [ 30 ]. In another LC-MS/MS method [ 29 ], 132 tested compounds were measured in honey, obtaining recoveries ranging from 70% to 120% for 116 compounds. However, the LOD and LOQ were not provided in the manuscript nor supplementary material [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations